Strategi Guru SKI dalam Memfasilitasi Keterampilan 4C pada Siswa di Madrasah - Aisa, Nur; Agustina, Tessa; Apriani, Anisa; Sufriadi, Rahmat (JPT : Jurnal Pendidikan Tematik, 2024)
The purpose of this study is to describe and explain the problems of learning Islamic Cultural History (SKI) for both teachers and students of MAN 2 Bengkulu City. This study was conducted using a qualitative approach. For example, data collection is done using several techniques. , observations, interviews and the addition of several documents. Strategy is science and art art of to use all the resources of a country to implement a specific policy of war and peace. Strategy is a guideline for planning military operations, such as organizing army and navy positions or battle strategies.